STUDI KASUS DROP OUT PENGOBATAN TUBERKULOSA (TB) DIPUSKESMAS KODYA MALANG - Hermayanti, Diah (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2010)
Abstract   Background: Direct Observed Treatment Short Course (DOTS) were used for Tuberculosa (TB) Control in Indonesia. Long time periode of treatment caused its drop out problem. Discontinuation of treatment and  inadequate doses increased  resistance and cost. Objective: To examine tuberculosis drop out treatment cases. Methods: Descriptive study. The data were collected with purposive random sampling. Results: There were  1372 patients TB in Malang, the number of  drop out cases were 137 patients (17%).  The patients who treatment at the puskesmas as many as 25 people (1.8%). Only  four people who successfully interviewed, because patient address data were incomplete.  The patient age ranged between 19-67 years, 75%  of patients were reproductive age, 25% were elderly, and 75% werefemale. The Big income were 100% below the minimum wage in Malang Municipality,  and 50% were unemployement. The patient education were 50% primary school graduates, 25% high school graduate, and 25% college graduate. The level of knowledge about TB disease were categorized 50% as good, 25% as moderate, and 25% as less category. The Health behavior in relation to drop out TB treatment: 50% due to the relatively faraway from  the clinic, and 50% felt tired of taking medicine every day. Other causes for the occurrence of side effects. Conclusion: The high dropout rate of TB treatment due to many factors including low income, low education, poor health behaviors, and drug side effect. Keywords: tuberculosa, DOTS, drop out